2020
DOI: 10.1007/s40825-020-00155-1
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Exhaust Transfer System Contamination on Particulate Matter Measurements

Abstract: As the measurement of low levels of particulate matter (PM) and solid particulate number (PN) from light-duty vehicles becomes more critical, it is becoming more important to understand the potential impacts of exhaust transfer system contamination. This phenomenon occurs when, as it relates to vehicle emission testing, particles deposit and semi-volatile materials are adsorb onto the inner surfaces of the exhaust transfer system, which includes the vehicle exhaust pipe, the exhaust transfer line, and the cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…It can be assumed that the released material nucleated during cooling and dilution in the full dilution tunnel and resulted in high particle concentrations. Such desorption and high concentration of nucleation mode particles was reported in a dedicated study on the influence of the transfer line on particulate emissions [15]. In our study the geometric mean dimeter of these particles was 17-24 nm.…”
Section: Discussionsupporting
confidence: 80%
“…It can be assumed that the released material nucleated during cooling and dilution in the full dilution tunnel and resulted in high particle concentrations. Such desorption and high concentration of nucleation mode particles was reported in a dedicated study on the influence of the transfer line on particulate emissions [15]. In our study the geometric mean dimeter of these particles was 17-24 nm.…”
Section: Discussionsupporting
confidence: 80%
“…At lower number concentrations in a few cases, higher percentages can be seen (the 80% values are from two WLTCs). The literature has also highlighted the need of stabilization time to the variability of the volatile particles measurements [56]: Many studies have found that it can take more than 1 h to stabilize the concentration of volatile particles [42,57], similar to what was demonstrated in our study. Other studies have also found higher concentration of volatile particles at the dilution tunnel compared to the tailpipe due to the desorption from the tube between the vehicle and the tailpipe [9,58].…”
Section: Emission Levelssupporting
confidence: 86%
“…Even though we used one filter for the whole campaign to minimize volatile artifacts on the filter, the PN/PM ratio was 3.8-4.8 × 10 11 p/mg, lower than the typically expected 1-2 × 10 12 p/mg, indicating that the contribution of volatiles was significant. We suspect that the origin is released material from the transfer tube to the dilution tunnel during the high exhaust gas temperature regeneration events [88].…”
Section: Pn Instrumentationmentioning
confidence: 99%